Analisis Pengaruh Pendidikan, PDRB Per Kapita, dan Tingkat Pengangguran Terhadap Jumlah Penduduk Miskin Provinsi Bali - Wirawan, I Made Tony; Arka, Sudarsana (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
Poverty is one of the problems often faced by people and the poverty problem as old as the age of humanity it self. The purpose of this study was to determine the effect of education, per capita GDP, and unemployment simultaneously and partially on the number of poor people, and to determine which variables are the most dominant influence on the number of poor people of Bali Province 2007-2013. The analysis technique used is multiple linear regression. Based on the analysis found that education, per capita GDP, and unemployment simultaneously significant effect on the number of poor people. Education partially negative effect on the number of poor population, GDP per capita is partially negative and significant effect on the number of poor people, while the unemployment rate is partially positive and significant effect on the number of poor. ariables that affect the most dominant on the number of poor people is the variable GDP per capita.
Keywords: Poverty, Education, GDP Per Capita, Unemployment.